Higher Prevalence of Non-thyroidal-Illness Syndrome in Elderly Male Patients With Active Helicobacter pylori Infection - Sun, Banruo; Wang, Xuanping; McLarnon, Michael Edmund David; Ding, Yu; Liu, Miao; Dai, Wei; Wang, Gangshi (Frontiers in Medicine, 2021)
Objective: It is currently unclear whether the Helicobacter pylori (H. pylori) infection leads to associated alterations in thyroid functions and thyroidal illnesses. This study aims to analyse this relationship in an elderly male cohort over a five-year period. Design: A case retrospective study. Methods: A longitudinal study was designed to collect subjects (≥65 years old) receiving both a thyroid examination and H. pylori infection status determined by 13C-urea breath test in 2013 at our unit. Subjects were followed every one to two years until December 2017 for laboratory results, visits to outpatient clinics/emergency departments etc. Blood tests and thyroid ultrasonography were performed to determine thyroid function and morphology. Results: 356 male subjects with mean age 78.5 ± 9.8 years were included. Active H. pylori infection was positive in 88 subjects (24.7%). Thyroid function tests and ultrasonography showed similar patterns between H. pylori positive and negative groups. Non-thyroidal-illness syndrome (NTIS) was diagnosed in 30/210 (14%) patients who experienced acute illnesses and hospitalization over five-year follow-up. Notably, NTIS demonstrated significantly higher prevalence in the H. pylori positive group compared to the negative group (17.1% vs. 5.6%, P = 0.001). Multivariate analysis showed that when age, APACHE II score and hemoglobin levels were adjusted, H. pylori status still has significant interrelationship with NTIS (OR = 3.497, P = 0.003). Conclusions: There is a positive association between chronic active H. pylori infection and NTIS prevalence in this elderly male cohort. Further studies are needed to elucidate the role of H. pylori infection on NTIS in elderly male patients.